A new species of the genus Odonteus (Coleoptera: Geotrupidae) from northern Pakistan - Carpaneto, Giuseppe M.; Mignani, Roberto (Zootaxa, 2005)
A remarkable new species, Odonteus gandhara Carpaneto & Mignani, n. sp., is described from northern Pakistan. The holotype (adult male) and the paratype (adult female) are illustrated and compared with O. armiger (Scopoli, 1772) and O. orientalis Mittal, 1998, the only two species of this genus recognized in the Old World. Both O. armiger and O. orientalis have the eye not completely divided by the canthus and have a sensory area on the external side of the last antennomere (this character has never been discussed in the literature until now). These two character states in O. armiger and O. orientalis compel emendations to the definition of the genus. The new species has a great zoogeographical relevance because similar species occur in North America (O. obesus LeConte, 1859 and O. falli Wallis, 1928), and probably represents a relict species endemic to the Himalayan range.